The Relationship Between Adversity Quotient and Career Adaptability of Internship Nursing Students - Annida Nur Shalihah; Kurniawan Yudianto; Nur Oktavia Hidayati (Universitas Padjadjaran, 2018)
A competitive job market is a challenge that needs to be faced by every university graduate. It is expected that every graduate has capability to keep face with expansion in job sectors. To be able to adapt to the job situation, a specific intelligence to face in facing every challenge and obstacle namely adversity quotient, is required. This study aimed to identify the correlation between adversity quotient (AQ) and career adaptability of internship nursing students. This study was descriptive correlational. Samples were recruited using a total sampling tecnique (n=142). Data were collected using a questionnaire consisting of a demographic survey, an Adversity Response Profile (ARP) Quick TakeTM and a Career Adapt-Abilities Scale (CAAS). Data were analyzed using descriptive statistics and Rank Spearman correlation test. The result of this study indicated that no students were in quitter category, only 0,7% of them were in quitter to camper transition, 76,8% of them were campers, 21,8% of the students were in camper to climber transition, 0,7% of all respondents were climbers. No students had a very low career adaptability, only 1,4% of them had a low career adaptability, while the proportions of students with a high and very high career adaptability were 75,4% and 23,2 % respectively. No significant correlation was found between AQ and career adaptability (p value >0,05; Spearman’s ρ +0,122). It can be concluded that most of internship nursing students at Faculty of Nursing Universitas Padjadjaran were campers and had a high level of career adaptability. There was also no significant correlation between AQ and career adaptability. Further research needs to explore about contributing factors related to career adaptability in internship nursing students.Keywords: Adversity quotient, career adaptability, internship nursing student. Hubungan Adversity Quotient dan Adaptabilitas Karier pada Mahasiswa Profesi NersAbstrakDalam menghadapi pasar kerja yang semakin ketat, setiap lulusan universitas diharapkan memiliki kemampuan untuk menghadapi tantangan dan beradaptasi dengan perkembangan pada dunia kerja. Untuk mengatasi hal tersebut diperlukan adanya kecerdasan dalam menghadapi setiap tantangan dan hambatan yang disebut adversity quotient (AQ). Penelitian ini bertujuan untuk mengetahui hubungan AQ dan adaptabilitas karier pada mahasiswa profesi ners. Penelitian ini menggunakan metode deskriptif korelatif. Responden penelitian berjumlah 181orang mahasiswa program profesi ners angkatan 32 dan 33 di Fakultas Keperawatan Universitas Padjadjaran yang di ambil dengan teknik total sampling dengan response rate 78,45%. Instrumen yang digunakan pada penelitian ini yaitu Adversity Response Profile (ARP) Quick TakeTM dan Career Adapt-Abilities Scale (CAAS). Teknik analisis data yang digunakan dalam penelitian ini menggunakan skoring ARP QuickTakeTM, skoring CAAS, serta uji korelasi Rank Spearman. Hasil penelitian menunjukkan bahwa tidak seorangpun responden yang berada pada kategori quitter, sebanyak 0,7% dari responden berada pada kategori transisi quitter ke camper, pada kategori camper sebanyak 76,8%, pada kategori transisi camper ke climber sebanyak 21,8%, dan pada kategori climber sebanyak 0,7%. Tidak ada mahasiswa dengan adaptabilitas karier sangat rendah, hanya 1,4% mahasiswa dengan adaptabilitas karier rendah, sedangkan mahasiswa dengan adaptabilitas karier tinggi dan sangat tinggi masing-masing proporsinya sebanyak 75,4% dan 23,2%. Tidak terdapat hubungan bermakna antara AQ dan adaptabilitas karier (p value >0,05; Spearman’s ρ +0,122). Simpulan dari penelitian ini yaitu sebagian besar mahasiswa profesi ners Fakultas Keperawatan Universitas Padjadjaran memiliki AQ dengan kategori camper dan memiliki adaptabilitas karier tinggi. Meskipun demikian, tidak terdapat hubungan bermakna antara AQ dan adaptabilitas karier. Bagi peneliti selanjutnya diharapkan untuk melakukan penelitian terkait faktor-faktor yang mempengaruhi adaptabilitas karier pada mahasiswa profesi ners.Kata kunci: Adversity quotient, adaptabilitas karier, mahasiswa profesi ners.